Прискорене моделювання стаціонарного розподілу кількості вимог у системі SMBAP|G|∞ - Shumska, A. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A queueing system with the infinite number of servers and batch arrival process controlled by the semi-Markov process is investigated. A fast simulation method for the evaluation of the steady-state distribution of the number of customers in the system is proposed, which is based on essential sampling and the central limit theorem. The estimates are asymptotically unbiased. The gain in variance compared to the Monte Carlo method is on the average two orders of magnitude.